Specifics and evaluation of the organisational and economic mechanism of industrial products regulated purchases in terms of ensuring their environmental safety - A. E. Gukasova (Вестник университета)
The research relevance is due to the tasks set in the Concept of Sustainable Development of the United Nations. One of the state mechanisms through which the state can influence both producers and buyers to develop socially responsible behavior, which would contribute to the greening of industrial products, could be the organisational and economic mechanism of regulated procurement. The aim of the study was to reveal the specifics and assess this mechanism in relation to industrial products in terms of ensuring its environmental safety. The study was methodologically based on general scientific research methods. A set of activities that make up the specifics of organising regulated procurement are considered and technical recommendations are developed. Particular attention is paid to life cycle contracts. An original system of indicators, characterizing the current performance of the mechanism under consideration, has been formed within the framework of the generally accepted characteristics. The system of indicators developed makes it possible to comprehensively assess the industrial products’ regulated purchases, focused on ensuring their environmental safety, and analyse the effectiveness of each element of regulated procurement organisation.